Straits of Chosun - Park Ki-chae; Lee Myeong-woo; Nam Seung-min; Moon Yae-bong; Kim Shin-jae (Taewon Entertainment, 2007)
A young man from a rich, noble family, Sung-ki has incurred the wrath of his parents by running off with Kinshuku, a woman from a poor family, against their wishes. When his brother dies in the war, Sung-ki repents his actions and decides to make amends by leaving Kinshuku and joining the army, unaware that she is pregnant. With a baby about to be born, Sung-ki’s sister Kiyoko tries to bring about a reconciliation between her family and Kinshuku, but the war and the stubborn pride of the noble family make this difficult. Extremely well photographed, artistically directed with a delicate touch that belies the melodramatic content, "Straits of Chosun" is by far the film that best achieves a balance between the its war message and the lives of ordinary people, between honour and duty to the family and the Japanese nation - although it is debatable whether this should be considered a good thing or not. [www.dvdtimes.co.uk]
Keywords: DVD-Video